Environmental effects of stratospheric ozone depletion, UV radiation and interactions with climate change: UNEP Environmental Effects Assessment Panel, update 2019. Issue 5 (4th May 2020) - Bernhard, G. H.; Neale, R. E.; Barnes, P. W.; Neale, P. J.; Zepp, R. G.; Wilson, S. R.; Andrady, A. L.; Bais, A. F.; McKenzie, R. L.; Aucamp, P. J.; Young, P. J.; Liley, J. B.; et al.
Abstract : This assessment provides an update of the interactive effects of solar ultraviolet (UV) radiation, stratospheric ozone, and climate change on human health, terrestrial and aquatic ecosystems, biochemical cycles, air quality, and material damage. Abstract : This assessment, by the United Nations Environment Programme (UNEP) Environmental Effects Assessment Panel (EEAP), one of three Panels informing the Parties to the Montreal Protocol, provides an update, since our previous extensive assessment ( Photochem. Photobiol. Sci., 2019, 18, 595–828), of recent findings of current and projected interactive environmental effects of ultraviolet (UV) radiation, stratospheric ozone, and climate change. These effects include those on human health, air quality, terrestrial and aquatic ecosystems, biogeochemical cycles, and materials used in construction and other services. The present update evaluates further evidence of the consequences of human activity on climate change that are altering the exposure of organisms and ecosystems to UV radiation. This in turn reveals the interactive effects of many climate change factors with UV radiation that have implications for the atmosphere, feedbacks, contaminant fate and transport, organismal responses, and many outdoor materials including plastics, wood, and fabrics. The universal ratification of the Montreal Protocol, signed by 197 countries, has led to the regulation and phase-out of chemicals that deplete the stratospheric ozone layer. Although this treaty has had unprecedented success in protecting the ozone layer, and hence all life on Earth from damaging UV radiation, it is also making a substantial contribution to reducing climate warming because many of the chemicals under this treaty are greenhouse gases.